Emergy accounting as a support for a strategic planning towards a regional sustainable milk production. (November 2019) - Agostinho, F.; Oliveira, M.W.; Pulselli, F.M.; Almeida, C.M.V.B.; Giannetti, B.F.
Abstract: Milk is one of the most important food in the world, being consumed in natura or supporting the dairy industry. In Brazil, specifically, the milk supply chain corresponds to about 20% of its agro-industrial gross domestic product; however, the productivity of most domestic milk production systems are still characterized as low. In view of this, the Brazilian government supports training programs to increase milk productivity and economic returns, however, sustainability issues are usually left in the background. This work uses emergy environmental accounting to study the sustainability of milk production systems in the southern region of Minas Gerais state, Brazil, aiming at two specific goals: (i) verifying their individual environmental performance based on emergy indices, and (ii) exploring alternatives for the development of milk production under a regional perspective. Results from a cluster analysis evidenced the existence of five main milk production systems in the region (G1–G5), including differences in productivity, handling, feed diet, infrastructure, and administrative control. Emergy indicators point to the G3 system (small-scale, family-managed) as the best performer concerning renewability (28%), yield (EYR 1.72), investment (EIR 1.39), environmental load (ELR 2.46), and sustainability (ESI 0.70); however, the G2 system should be promoted when equally considering ESI and efficiency for a decision. Under a regional perspective, increasing milk productivity will also increase a system's dependence on fossil-based resources, which results in an uneven emergy matching and in a less efficient use of emergy. On the other hand, pursuing the increase of sustainability for milk production by optimizing the regional EIR would result in an expansion of the G3 system in 96% of all milking areas and the production would decrease by about 57%. Such trade-off claims for different policies in accordance with societal objectives in different periods. Besides diagnosing and ranking the milk production systems according to their environmental performance, this work also provides important subsidies for decision-makers regarding a strategic plan towards a sustainable milk production under a regional perspective. Highlights: Emergy synthesis is applied to five different milk production systems in Brazil. A trade-off exist between milk productivity and its environmental performance. Emergy is used to support a regional strategic planning towards sustainable milk production. Results provide important subsidies for public policies in a scenario without fossil energy.